EFEKTIVITAS KELAS IBU HAMIL TERHADAP DETEKSI DINI TANDA BAHAYA KEHAMILAN - Titik Wijayanti; Atik Setiyaningsih (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
The high maternal mortality rate (MMR) in Boyolali seen from the data in 2012 there were 15cases of maternal deaths and up to mid-2013 there have been five cases of maternal death,Cause of death cases in Boyolali such as hypertension, bleeding, PEB and hepatitis. (DinkesKab. Boyolali, 2013). The causes of maternal death, can be prevented with early detectionthrough a class of pregnant women at the village level which is a program launched by thegovernment since 2009 This research is a quasi experimental design with pretest-posttest Onegroup, where groups of pregnant women are given pre-test first, then given a class treatpregnant women 4 times meeting and ending with post-test. Respondents were a total of 30pregnant women, taken by purposive sampling technique. Data were analyzed using paired ttest. The results showed during the pre-test, respondents who have skills in early detection inboth categories (76% - 100%) by 6 respondents (20%), and at post-test, the ability of therespondent in the early detection of both categories increased to 16 respondents (53.3%). Theresults of the analysis by paired t test showed the value of ρ-value (0,00) <α (0.05) which meansthat classes effectively improve the ability of pregnant women in the early detection of dangersigns of pregnancy. Correlation value of 0.762 indicates that the class of pregnant women havea strong influence on the early detection of danger signs of pregnancy.Key word: class of pregnant women, early detection, the danger signs of pregnancy